Group formation, relatedness, and the evolution of multicellularity. - Fisher, R; Cornwallis, C; West, SA (2013)
The evolution of multicellular organisms represents one of approximately eight major evolutionary transitions that have occurred on earth. The major challenge raised by this transition is to explain why single cells should join together and become mutually dependent, in a way that leads to a more complex multicellular life form that can only replicate as a whole. It has been argued that a high genetic relatedness (r) between cells played a pivotal role in the evolutionary transition from single-celled to multicellular organisms, because it leads to reduced conflict and an alignment of interests between cells. We tested this hypothesis with a comparative study, comparing the form of multicellularity in species where groups are clonal (r = 1) to species where groups are potentially nonclonal (r ≤ 1). We found that species with clonal group formation were more likely to have undergone the major evolutionary transition to obligate multicellularity and had more cell types, a higher likelihood of sterile cells, and a trend toward higher numbers of cells in a group. More generally, our results unify the role of group formation and genetic relatedness across multiple evolutionary transitions and provide an unmistakable footprint of how natural selection has shaped the evolution of life.